Producción, comercialización y rentabilidad de la tilapia roja (oreochromissp) en la parroquia Guasaganda y su relación con la economía del cantón La Maná provincia de Cotopaxi año, 2011 - Vega Zoto, Marina Rosario (2013)
The purpose of this research in Guasaganda parish allowed to know the disadvantages that every single producers has in fish production during the year 2011. The study of the marketing and profitability of red tilapia identified the amount of production that exists in the parish and the utility that generates this activity. In order to obtain information, it was necessary the use of surveys which were applied to producers and consumers, so determining that there are 14 red tilapia producers. In addition, their activity is focused in raising tilapia for marketing, so it represents an increase of fish production.